Usability and organizational factors in radiology systems: a study with health professionals in Brazil - Silva, Fábio Aparecido Cândido da (2022)
Medical systems have been increasingly important in medical practice and clinical interventions and are crucial for physicians and other health professionals to perform their routine activities in a hospital environment. Such systems include such as HIS (Hospital Information System), RIS (Radiology Information System) and PACS (Picture Archiving and Communication System), for instance. In Radiology, for example, proper usability and alignment with the tasks of these systems are essential, as they often involve thorough analyses that require attention to detail and complex image manipulation techniques for diagnosis. The images generated and manipulated by radiology systems are essential assets to support diagnosis in the health area. However, these radiology systems may present usability problems in handling. Considering the complexity of the tasks and the effects that errors can have, usability problems can be harmful, as they compromise the efficiency of the process, generating incorrect diagnoses and delays in service and results. Despite some research on radiology systems in several countries, few studies report usability in small and medium-sized health facilities, especially in the Brazilian context. This study evaluated organizational factors and the usability of radiology systems in the Brazilian scenario and compared the findings with the results of usability evaluations in the literature. The issues identified in this study are essential to improve the interaction of health professionals in more complex activities. The study involved interviews with ten health professionals from different regions of Brazil and remote usability evaluations of a radiology system with six professionals. The study aims to fill gaps, such as identifying the challenges for designers and the interaction of radiology systems in Brazil. Interviews with radiology professionals resulted in five themes: “How the characteristics of the radiology system affect usability for the user”, “How situations or processes affect the characteristics of radiology professionals’ tasks”, “What influences the behavior of the radiology professional concerning their routine”, “What determines a radiology professional’s experience and knowledge”, and “Radiology professionals deal with system failures and data loss risk”. These themes describe the factors that interfere in the radiology professional’s routine and their interaction with radiology information systems. Usability testing resulted in 20 categories of usability issues organized into four themes: “Visual Presentation”, “Content”, “Information Architecture”, and “Interactivity”.The results consolidate a set of recommendations for the design and evaluation of radiology systems. They incorporate the aspects identified and related to the Brazilian context, the variety of availability of resources in health facilities, which are still limited in the sense of being based on textual descriptions of problems reported in the literature and not in detailed tests.